Private Health Insurance in Poland as a Response to Increasing Cancer Costs - Marta BORDA (Communications of International Proceedings, 2020)
Demographic factors, epidemiological factors, and persistently low level of financing for oncological treatment in Poland create opportunities for further development of private health insurance providing services in the event of cancer. The purpose of this paper is to provide an overview of private health insurance products that are available in Poland for covering the various financial consequences associated with cancer risk. The study confirmed among others that most insurance is provided in lump sum benefits, pointing to a need for further development of current product offer, especially in the field of products that ensure compensation for incurred costs and income loss.
Keywords: Private Health Insurance; Oncological Treatment; Cancer Risk.